Genetic diagnoses and associated anomalies in fetuses prenatally diagnosed with esophageal atresia. Issue 8 (23rd June 2020) - Rohanizadegan, Mersedeh; Tracy, Sarah; Galarreta, Carolina I.; Poorvu, Tabitha; Buchmiller, Terry L.; Bird, Lynne M.; Estroff, Judy A.; Tan, Wen‐Hann
Abstract: Esophageal atresia (EA) is a congenital anomaly occurring in 2.3 per 10, 000 live births. Due to advances in prenatal imaging, EA is more readily diagnosed, but data on the associated genetic diagnoses, other anomalies, and postnatal outcome for fetuses diagnosed prenatally with EA are scarce. We collected data from two academic medical centers ( n = 61). Our data included fetuses with suspected EA on prenatal imaging that was confirmed postnatally and had at least one genetic test. In our cohort of 61 cases, 29 (49%) were born prematurely and 19% of those born alive died in the first 9 years of life. The most commonly associated birth defects were cardiac anomalies (67%) and spine anomalies (50%). A diagnosis was made in 61% of the cases; the most common diagnoses were vertebral defects, anal atresia, cardiac anomalies, tracheoesophageal fistula with esophageal atresia, radial or renal dysplasia, and limb anomalies association (43%, although 12% met only 2 of the criteria), trisomy 21 (5%), and CHARGE syndrome (5%). Our findings suggest that most fetuses with prenatally diagnosed EA have one or more additional major anomaly that warrants a more comprehensive clinical genetics evaluation. Fetuses diagnosed prenatally appear to represent a cohort with a worse outcome.